Unpacking Prior Experience: How Career History Affects Job Performance - Dokko, Gina; Wilk, Steffanie L; Rothbard, Nancy P (Organization science (Providence, R.I.), 2009)
As individuals change jobs more frequently, it is increasingly important to understand what they carry from their prior work experience that affects their performance in a new organizational context. So far, explanations about the imperfect portability of experience have primarily been about firm specificity of knowledge and skill. We draw on psychological theory to propose additional sociocognitive factors that interfere with the transfer of knowledge and skill acquired from prior related work experience. As we hypothesized, we find that task-relevant knowledge and skill mediates the relationship between prior related experience and job performance and that it acts as suppressing mediator of a negative direct relationship between prior related experience and current job performance. We also find that the positive effect of prior related experience on task-relevant knowledge and skill is attenuated by higher levels of experience within the current firm.